1981
DOI: 10.1104/pp.67.4.859
|View full text |Cite
|
Sign up to set email alerts
|

Methylammonium Transport in Phaseolus vulgaris Leaf Slices

Abstract: Methylammonium (as a nonmetabolized analog of ammonium) transport was studied in leaf slices of Phaseolus vulgaris L. var. 'Hawkesbury Wonder.' The relationship of influx to external pH (6.0-10.5) shows that the influx at low external pH is a larger fraction of that at high external pH than would be expected from the pK. of methylammonium and the assumption that only CH3NH2 is entering the cells. The relationship between methylammonium influx and external methylammonium concentration shows some evidence of sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Howitt and Udvardi (2000), however, propose that LATS transport occurs via a reversible NH 3 transporter. In support of this proposal, the authors cite a study of 14 C-methylamine (CH 3 NH 2 /CH 3 NH 3 ϩ ) uptake by Phaseolus vulgaris leaves (Raven and Farquhar, 1981), but in fact this study showed that the relationship of influx to external pH and the equilibrium concentration of methylamine were "far higher than could be explained by the transport of CH 3 NH 2 alone." Raven and Farquhar concluded that methylamine uptake, at least at pH values below 7, was predominantly as CH 3 NH 3 ϩ , and driven by the membrane electrical potential difference (⌬).…”
Section: Passive Diffusion Of Nh 3 Through An Lats?mentioning
confidence: 81%
“…Howitt and Udvardi (2000), however, propose that LATS transport occurs via a reversible NH 3 transporter. In support of this proposal, the authors cite a study of 14 C-methylamine (CH 3 NH 2 /CH 3 NH 3 ϩ ) uptake by Phaseolus vulgaris leaves (Raven and Farquhar, 1981), but in fact this study showed that the relationship of influx to external pH and the equilibrium concentration of methylamine were "far higher than could be explained by the transport of CH 3 NH 2 alone." Raven and Farquhar concluded that methylamine uptake, at least at pH values below 7, was predominantly as CH 3 NH 3 ϩ , and driven by the membrane electrical potential difference (⌬).…”
Section: Passive Diffusion Of Nh 3 Through An Lats?mentioning
confidence: 81%
“…To investigate the transcript response to alterations in organic acid levels, an established leaf slice system was applied (Raven and Farquhar, 1981;Muller et al, 2001;Horling et al, 2003) that allows quick and efficient feeding of organic acids and other effector solutions to leaves. The microarray experiments from feeding low levels of citrate and malate (1 mM each) revealed that both organic acids convey an overall very different transcriptome response and that only a small set of transcripts such as AOX1a is regulated by both organic acids (Fig.…”
Section: Alterations In Citrate and Malate Levels Results In Unique Trmentioning
confidence: 99%
“…The leaf slice system has been used for gene expression analysis in several previous studies (Raven and Farquhar, 1981;Horling et al, 2003). It allows a fast and homogenous application of effector solutions.…”
Section: Citrate Has a Stronger Effect On Transcript Abundances Than mentioning
confidence: 99%
“…Transport of NH4+ across plasmalemma of mesophyll cells thus seems to be rapid relative to that across plasmalemma of root cells. Raven and Farquhar (1981) and Karasawa et al (1994) suggested that NH4+ was transported across the leaf plasmalemma by an uniport, actively controlling the NH,+ and NH3(aq) concentration in the apoplast via induction/ repression and feedback inhibition. The NH,' concentration in leaves of B. napus ranged from 0.4 to 1.3 mM in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…3) Hours from start of experiment Farquhar (1981) (Wang et al, 199313). Transport of NH4+ across plasmalemma of mesophyll cells thus seems to be rapid relative to that across plasmalemma of root cells.…”
Section: Discussionmentioning
confidence: 99%